Fundamentals of entrepreneurship ENT300 : Proposal café and books / Hixmmien Mujah ... [et al.] - Mujah, Hixmmien; Uslan, Nalisha Laila; Jelian, Christina Bunsi; Yong, Sendy; Jadan, Eurecca (2011)
Cafe and books that is name of our company that offers products by selling and renting books as well as re-selling used books in order to support the "Green" effort to save the nature as well. We also offer services of selling food and beverages in our café. Our company is a partnership business that will opening our first branch in The Hills Mall Kuching, Sarawak situated in Jalan Mathies. The shop lot will be divided into two spaces consisting of a bookstore as well as a café. Our bookstore will offèr various choices of books from local as well as International publication houses tor various genres. En suite our bookstore will be a café which offers light snacks such as sandwiches, chicken wings, burgers and also local favourites such as banana fritters. We Will also be selling patisseries, cupcakes and cakes which will be ready-made by our caterers. We will also offer made-to-order tea, coffee and milo blended and as also fresh fruit juices.